Attitudes and perceptions of mothers towards childhood vaccination in Greece: lessons to improve the childhood COVID-19 vaccination acceptance - Fakonti, Georgia; Hadjikou, Andria; Tzira, Eleana; Kyprianidou, Maria; Giannakou, Konstantinos (Frontiers in Pediatrics, 2022)
Background: Maternal attitudes and beliefs have been shown to influence childhood vaccination coverage, resulting in under-vaccination, non-vaccination, and vaccination delay. This study aimed to investigate the mothers’ attitudes and perceptions about vaccination for their children in Greece. Methods: This was an online cross-sectional study, conducted from 4 April to 8 June 2020. A self-administered questionnaire was used to collect information about mothers’ and their children’s socio-demographic characteristics, previous vaccination behavior, and mothers’ attitudes and perceptions about childhood vaccination. Participants included adult mothers with at least one minor child. Results: 1885 mothers participated, with the majority (91.7%) believing in the usefulness of vaccines and that vaccines protect children from serious and life-threatening diseases. A larger percentage of mothers with higher educational attainment agree/absolutely agree that all vaccinations provided by the National Vaccination Program must be offered to our children (91.6%) (p=0.02) and that vaccines protect children from serious and life-threatening diseases (92.9%) (p=0.01). Significant more married/in cohabitation and not single-parent mothers agreed that vaccines are safe (53.5% and 53.4%, respectively). There were also several significant associations between maternal attitudes toward childhood vaccination and previous maternal vaccination practices [(e.g., adherence to recommended vaccination dosages (all p-values<0.01), vaccination delays (all p-values<0.05), and vaccination during pregnancy (all p-values<0.01)]. Conclusion: Maternal attitudes and perceptions toward childhood vaccination are significantly influenced by sociodemographic factors and maternal vaccination practices. Revealing those is essential for public health officials in developing future strategies to improve childhood vaccination coverage and acceptance of new vaccines such as the COVID-19 vaccine.